«Skin window» cytokines in atopic dermatitis - D. S. Zagreshenko; V. V. Klimov; A. A. Denisov; T. I. Salikova; Ye. K. Firsova (Бюллетень сибирской медицины, 2009)
There have been defined IL-4, IL-10, IL-17 and IFN-γ in cell-free skin exudate in 90 patients of atopic dermatitis depending on spread of dermal pathological process. There been found that variations of each cytokine had different features and reflected different parts of immunopathogenesis of the disease both in an acute period and remission and after allergenspecific immunotherapy.